2019
DOI: 10.1002/dvg.23323
|View full text |Cite
|
Sign up to set email alerts
|

Generation of conditional ALK F1174L mutant mouse models for the study of neuroblastoma pathogenesis

Abstract: Neuroblastoma, an embryonal tumor arising from the sympathetic ganglia and adrenal medulla, is among the most intractable pediatric cancers. Although a variety of genetic changes have been identified in neuroblastoma, how they contribute to its pathogenesis remains largely unclear. Recent studies have identified alterations of the anaplastic lymphoma kinase (ALK) gene in neuroblastoma; ALK F1174L (a phenylalanine-to-leucine substitution at codon 1174) represents one of the most frequent of these somatic mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
4
16
0
Order By: Relevance
“…Further observation of heterozygous (n = 13 > 18 months) and homozygous (n = 19 > 18 months) Alk-F1178S animals up to 18 months of age did not reveal development of NB or any other type of cancer. Thus, while no gross tumour development is observed in Alk-F1178S mice, significant hyperplasia can be detected in Alk expressing neural crest-derived structures during development, such as the sympathetic ganglia, which is in agreement with other reports (Cazes et al, 2014;Ono et al, 2019).…”
Section: ª 2021 the Authorssupporting
confidence: 93%
See 2 more Smart Citations
“…Further observation of heterozygous (n = 13 > 18 months) and homozygous (n = 19 > 18 months) Alk-F1178S animals up to 18 months of age did not reveal development of NB or any other type of cancer. Thus, while no gross tumour development is observed in Alk-F1178S mice, significant hyperplasia can be detected in Alk expressing neural crest-derived structures during development, such as the sympathetic ganglia, which is in agreement with other reports (Cazes et al, 2014;Ono et al, 2019).…”
Section: ª 2021 the Authorssupporting
confidence: 93%
“…Alk‐F1178S homozygous mice were obtained with expected Mendelian ratios, and a colony of Alk‐F1178S mice was established. Since previous reports of Alk gain‐of‐function mice have reported hyperplasia in the sympathetic ganglia (Cazes et al , 2014; Ono et al , 2019), we investigated ganglia from Alk‐F1178S mice and WT siblings at developmental stage P9. Alk‐F1178S heterozygous caeliac ganglia were significantly enlarged and displayed hyperplasia when compared with controls, which was enhanced in Alk‐F1178S homozygous animals (Fig 3A–C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this was challenged in 2014, when Cazes et al showed that ALK F1174L and ALK R1275Q variants indeed lead to abnormal proliferation of sympathetic ganglia, but were not sufficient to initiate neuroblastoma formation. This suggests a requirement for additional factors, such as MYCN amplification, to trigger tumorigenesis [89,90]. Increased MYCN activity is likely to enhance neuroblast proliferation and survival [91].…”
Section: Alk and Mycn In Neuroblastomamentioning
confidence: 99%
“…Increased MYCN activity is likely to enhance neuroblast proliferation and survival [91]. Following this, ALK activation may potentiate the oncogenic capacity of MYCN [17,90,[92][93][94]. These two factors are the most common predisposition markers of neuroblastoma and, together, are associated with poor prognosis [77,95].…”
Section: Alk and Mycn In Neuroblastomamentioning
confidence: 99%